Analisis materi bahasa Indonesia berbasis pendidikan karakter dalam buku peserta didik kelas iv sd tema 3 "peduli terhadap makhluk hidup" - Aisyah, Diah Estry Nur; Winarni, Retno; Surya, Anesa (Didaktika Dwija Indria, 2021)
This research aims to explain The Indonesian language learning material and character education-based language skills in the grade IV elementary school student book on the 2013 Curriculum theme "Peduli terhadap Makhluk Hidup". This type of research was qualitatively descriptive with the method of content analysis. The data in this research were 10 character values according to Permendikbud No. 20 of 2018, namely: tolerance, discipline, hard work, creative, independent, democratic, friendly/communicative, environmental care, social care, and responsibility. This research focused only on learning material Bahasa Indonesia in grade 4 elementary school students' book with the theme 3 revised edition 2017. The results of this research were known that there are 10 character values in Indonesian material in the student's book and contain all four language skills. The frequency with which character education values and language skills are presented is not evenly presented. The value of character education was dominated by the values of tolerance, creative, democratic, and friendly/communicative, while language skills are emphasized more on speaking and writing skills.Keywords: character education, Indonesian learning material, language skills, student’s book, elementary school.